An investigation of raw and torrefied lignocellulosic biomasses with CaO during combustion. Issue 4 (August 2018) - Roy, Poritosh; Dutta, Animesh; Acharya, Bimal; Deen, Bill
Abstract: The thermal degradation of three categories of raw and torrefied biomass [agri-residue: wheat straw, forest residue: sawdust, energy crop: miscanthus] was studied in a TGA-FTIR system with or without catalyst (CaO). The thermal degradation of biomass was carried out in the temperature range of 25–900 °C at a heating rate of 20 °C/min. The air flow rate was controlled based on the stoichiometric air requirement for complete combustion. The non-linear regression (NLREG) model was adopted to determine the kinetic parameters. The weight loss, heat flow, maximum weight loss temperature, and activation energy were observed to be dependent on the types of biomass and the process parameters. The maximum weight loss temperature was higher for torrefied biomass compared with raw biomass. The activation energy was higher in the case of torrefied biomass compared with raw biomass, and CaO helped to shrink the activation energy. The maximum weight loss temperature and activation energy were varied from 310 to 509 °C and 15–85 kJ/mol, respectively. The CaO supplement seems to have a positive impact on the thermal degradation process; thus, it may help in improving the thermal degradation process of torrefied biomass. Highlights: Thermal degradation of treated and untreated biomass was analyzed. Three categories of biomass were degraded with and without catalyst (CaO). TGA-FTIR was used to evaluate the degradation performances of biomass. The thermal degradation performance seems to be influenced by process parameters. The activation energy of feedstock can be reduced by incorporating CaO.